Effects of a Seven-Week App-Based Passive Psychoeducation Program on Perceived Stress in Nursing Students—A Randomized Controlled Parallel-Group Study - Elisabeth M. Weiss; Markus Canazei; Siegmund Staggl; Laura Staller; Katharina Kreiger; Bernhard Holzner; Verena Dresen (Nursing Reports, 2026)
Background/Objective: Web-delivered psychoeducational tools offer scalable options for managing elevated stress. Passive psychoeducation that delivers self-guided content without active psychotherapy techniques or homework may be particularly accessible at low costs. The present study examined the acceptability and preliminary effectiveness of a seven-week app-based passive psychoeducational stress-management program in an unselected cohort of nursing students. Methods: In this parallel-group randomized controlled trial (preregistered at the German Clinical Trials Register), 154 nursing students were randomized to either a psychoeducation group (n = 77) or a waitlist control (n = 77). Outcomes were assessed at baseline and post-intervention using the Depression Anxiety Stress Scales–21 (DASS-21). A total of 56 completed the post-test assessment. The intervention group received a new psychoeducational module each week for seven weeks. After each module, participants rated satisfaction and reported adherence and application of content in daily life. The control group received no intervention. Results: Compared with the waitlist control, the intervention group showed a statistically significant reduction in perceived stress from pre- to post-test. Depressive symptoms demonstrated a trend toward improvement, whereas anxiety scores did not change significantly. Acceptability ratings were high and participants reported moderate uptake of strategies and perceived relief. Conclusions: A brief, app-based passive psychoeducational program appears feasible and acceptable for nursing students and can reduce perceived stress. However, the findings of the current study should be interpreted cautiously given the high attrition rate and the absence of long-term follow-up. Further studies with larger samples and replication under conditions of better retention are warranted.